2019
DOI: 10.1038/s41598-019-54264-1
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in the near-field feeding current of a calanoid copepod are useful for particle sensing

Abstract: Calanoid copepods are small crustaceans that constitute a major element of aquatic ecosystems. Key to their success is their feeding apparatus consisting of sensor-studded mouth appendages that are in constant motion. These appendages generate a feeding current to enhance the encounter probability with food items. Additionally, sensing enables the organism to determine the position and quality of food particles, and to alter the near-field flow to capture and manipulate the particles for ingestion or rejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Mechanosensitivities is higher for species inhabiting quiet environment [4]. Sensing is so precise that it enables the organism to determine the position and quality of food particles, and to alter the near-field flow to capture and manipulate the particles for ingestion or rejection [5,6]. It was also shown that temperature changes impact the mechanosensitivity of small zooplankton, more than the thermally-induced effects on metabolism [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanosensitivities is higher for species inhabiting quiet environment [4]. Sensing is so precise that it enables the organism to determine the position and quality of food particles, and to alter the near-field flow to capture and manipulate the particles for ingestion or rejection [5,6]. It was also shown that temperature changes impact the mechanosensitivity of small zooplankton, more than the thermally-induced effects on metabolism [7].…”
Section: Introductionmentioning
confidence: 99%
“…Last, we have focused on the sensing of hydrodynamic disturbances caused by the mismatch between the rigid body motion of a prey particle and the deformational flows of feeding currents. Another possible mechanism of sensing may be the phase mismatch of non‐neutrally buoyant particles with the oscillatory feeding current (Giuffre et al 2019). In that case, additional hydrodynamic signals arising from the net force exerted on the fluid by the weight of the particle are unavoidable and could also be sensed by the copepod.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions (i.e., making contact with and handling of or manipulating particles) were previously documented in detail through observation under a binocular microscope [ 19 28 ]. In this context, setae morphology and mesh size of the filtering structure and the surface chemistry and forces (e.g., van der Waals forces) of feeding structures and particles are of high importance, especially when the particles are of smaller diameter than the meshes of the sieve [ 14 , 29 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…To test how the feeding efficiency depends on the mechanical property gradients and the adhesion forces of the setae, we here present a numerical model that simulates the interplay between setae during suspension feeding. In the past, numerical simulations were used to study the detection of prey, mates, or predators and the feeding current generation by limb motion [ 28 , 39 41 ]. However, mechanical property gradients and adhesion of setae were previously not addressed.…”
Section: Introductionmentioning
confidence: 99%